Digital Avatars: A Metaphenomenological Approach of Immersion - Kalligeris, Ioannis; Chrysopoulos, Panagiotis (Conatus - Journal of Philosophy, 2017)
This paper examines digital avatars as an advanced form of the virtual self in a digital environment of three and more dimensions. With this definition, we proceed to a post-phenomenological analysis of Avatar's space of action, i.e. the cyberspace and Avatar's dependence on its user. The writers will try to prove that Avatars are incomplete consciousness that cannot be emancipated by its user. Also, by studying the user's immersion in the digital environment, this process will be presented as a kind of self-identification with his avatar. Thus, it will help the reader to understand the relationship between the physical and the digital reality by presenting the function of human consciousness in the digital environment as Avatar´s consciousness during the stage of meta-vithisis (post-immersion).